The Fatty Acid Profile Of Sparus Aurata Larvae Is Correlated To The Composition Of The Enrichment Diets Of Brachionus Plicatilis And Artemia sp - Posau-Ferreira, P.; Cairrao, F.; Nery, F.; Narciso, L. (Ciencias Marinas, 1997)
El objetivo del presente estudio fue determinar el efecto del enriquecimiento de rotíferos (Brachionus plicatilis) y camarones de salina (Artemia sp.) con diferentes emulsiones comerciales y microalgas sobre la composición de los ácidos grasos poliinsaturados (PUFA) de larvas de pargo dorado, Sparus aurata. Se alimentaron los rotíferos con cuatro dietas de enriquecimiento (Chlorella sp. marino y tres emulsiones comerciales: Algal RotíferoMR, FrippakMR Booster y SelcoMR). Se realizó el enriquecimiento de Artemiu sp. (Artemia SystemsMR, tipo AF) con nauplios instar I a una densidad de 250-300 nauplios/ml en estanques cónicos de 20 l, usando dos emulsiones comerciales (TrofficMR y SelcoMR) y una microalga (Chlorella sp.). A pesar de que el método de enriquecimiento parece ser eficiente para incorporar el tratamiento de ácidos grasos en las larvas, los resultados muestran que las presas enriquecidas tuvieron una deficiencia de PUPA n-3 y que posiblemente no aportan los requisitos alimenticios de las larvas de pargo dorado. The objective of the present work was to determine the effect of the enrichment of rotifers (Brachionus plicatilis) and brine shrimp (Artemia sp.) with different commercial emulsions and microalgae on polyunsaturated fatty acid (PUFA) composition of gilthead sea bream larvae. Sparus aurata. Rotifers were fed four enrichment diets (marine Chlorella sp., and three commercial emulsions: Algal RotíferoTM, FrippakrTM booster and SelcoTM). The enrichment of Artemia sp. (Artemia SystemsTM, AF type) was carried out with instar 1 nauplii at a density of 250-300 nauplii/ml in 20-l conical tanks, using two commercial emulsions (TrofficTM and SelcoTM) and a microalgae (Chlorelia sp.). The results showed that enriched preys were deficient in PUFA n-3 and may not provide the nutritional requirements of sea bream larvae, although the enrichment methodology seems to be efficient in order to incorporate in the larvae the fatty acid treatment.